Incidence, Risk Factors and Prevention Related to Infusion Phlebitis (Journal of Pharmaceutical Negative Results, 2022)
Phlebitis linked with peripheral venous catheters is caused by inflammation of the vein at the cannula access site. It could be caused by mechanical, chemical, or pathogenic agents. Phlebitis can be avoided by adhering to best practises when inserting a cannula, such as selecting the right device and placement. Document the incidence of phlebitis and explore the risk factors linked with it. Analysis of existing data from a major randomised controlled trial. The primary goal of which was to compare routine peripheral intravascular catheter replacements with catheter replacements based solely on clinical indication. Patients hospitalised to the medicine and surgery ward, which required an intravenous catheter in the periphery were the part of study. 13283 PIVCs were investigated. During intravenous infusion, 41 (0.1%), and 48 hours after chemotherapy infusion, 35 (1.3%), paediatric patients were diagnosed with phlebitis. Postinfusion phlebitis can be problematic; therefore, it is essential for medical professionals to inform patients of what to watch for after the removal of an intravascular device.